Facing death : familial responses to illness and death - Scott, Christina L.; Williams, Heidi M.; Wilder, Siri (Contemporary perspectives on family research, 2022)
While rituals surrounding death may vary by geography, culture, and time, experiencing the loss of a loved one is a universal experience. Death has become a focal point during the ongoing COVID-19 pandemic, forcing many to unexpectedly confront the profound and enduring reality of loss. Understanding death from a multidisciplinary approach, Facing Death compiles contributions from across fields, methodologies, locations, cultures, and circumstances. Facing Death explores beyond loss solely on an individual level, considering instead helpful or harmful emotional reactions from others. Delving into how older adults who experience loss may find themselves without a support system, while those at a young age might find that their peers do not understand or know how to support them in their bereavement, the authors also consider how causes of death can also affect grieving loved ones on a personal and societal level. For example, how might death by suicide complicate the grieving process as family and friends not only have to contend with the loss itself, but also the associated stigmas and judgements surrounding suicide? How might individuals experience fear and anxiety about death during a prolonged illness? Exploring responses to familial illness and death, this edited collection is a detailed investigation of the subject for any scholar interested in discussions and decisions surrounding end of life care and the grief trajectory after loss.